HUMAN PAPILLOMA VIRUS. PREVENTION OF HPV-ASSOCIATED DISEASES - F. C. Shakhtakhtinskaya; L. S. Namazova-Baranova; V. K. Tatochenko; D. A. Novikova; N. E. Tkachenko (Union of pediatricians of Russia, 2015)
High prevalence of sexually transmitted diseases among the population attracts attention of specialists in all countries due to frequent development of complications resulting in reproductive dysfunction. The article presents one of the urgent issues of modern medicine - papillomavirus infection, which is the most common sexually transmitted disease. 70-80% of the sexually active persons contract human papilloma virus at one point. HPV induces a broad range of oncological reproductive diseases, including cervical, vulvar, vaginal and anal cancer and anogenital condylomae, which are observed both in men and women. The only reliable method of preventing papillomavirus infection is vaccination. The authors present new data on the use of the quadrivalent vaccine, including a new immunization pattern for 9-14-years-old girls.